Field emission properties of highly ordered low-aspect ratio carbon nanocup arrays - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Singh, Satbir; Suryawanshi, Sachin R.; Agrawal, Neetu; Gupta, Govind; Kim, Ah Ra; Gupta, R. K.; More, Mahendra A.; Late, Dattatray J.; Hahm, Myung Gwan (RSC Advances, 2016)
Herein, we design and develop a field emission device utilizing highly porous carbon nanocup (CNC) films. These three-dimensional (3D) low-aspect ratio CNC structures were fabricated by a combination of anodization and chemical vapor deposition techniques. The low turn-on fields of 2.30 V mu m(-1) were observed to draw an emission current density of 1 mu A cm(-2) and a maximum emission current density of similar to 1.802 mA cm(-2) drawn at an applied field of similar to 4.20 V mu m(-1). The enhanced field emission behavior observed from the CNC films is attributed to an excellent field enhancement factor of 1645. The observed field emission properties of CNC arrays are attributed to a synergistic combination of high aspect ratio, nano-sized radius of curvature, highly organized distribution of the emitters over the whole area of specimen and lower screening effect of the CNC arrays. These observations shed light on the effect of the stacking carbon layers of CNC on their electronic properties and open up possibilities to integrate new morphologies of graphitic carbon in nanotechnology applications. Thus, the low turn on field, high emission current density and better emission current stability enable CNC based future field emission applications.

High-performance field emission device utilizing vertically aligned carbon nanotubes-based pillar architectures - Gupta, Bipin Kumar; Kedawat, Garima; Gangwar, Amit Kumar; Nagpal, Kanika; Kashyap, Pradeep Kumar; Srivastava, Shubhda; Singh, Satbir; Kumar, Pawan; Suryawanshi, Sachin R.; Seo, Deok Min; Tripathi, Prashant; More, Mahendra A.; et al. (AIP Advances, 2018)
The vertical aligned carbon nanotubes (CNTs)-based pillar architectures were created on laminated silicon oxide/silicon (SiO2/Si) wafer substrate at 775 degrees C by using water-assisted chemical vapor deposition under low pressure process condition. The lamination was carried out by aluminum (Al, 10.0 nm thickness) as a barrier layer and iron (Fe, 1.5 nm thickness) as a catalyst precursor layer sequentially on a silicon wafer substrate. Scanning electron microscope (SEM) images show that synthesized CNTs are vertically aligned and uniformly distributed with a high density. The CNTs have approximately 2-30 walls with an inner diameter of 3-8 nm. Raman spectrum analysis shows G-band at 1580 cm(-1) and D-band at 1340 cm(-1). The G-band is higher than D-band, which indicates that CNTs are highly graphitized. The field emission analysis of the CNTs revealed high field emission current density (4mA/cm(2) at 1.2V/mu m), low turn-on field (0.6 V/mu m) and field enhancement factor (6917) with better stability and longer lifetime. Emitter morphology resulting in improved promising field emission performances, which is a crucial factor for the fabrication of pillared shaped vertical aligned CNTs bundles as practical electron sources. (c) 2018 Author(s).

Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions